Expectations of recovery: A prognostic factor in patients with neck pain undergoing manual therapy treatment. (31st March 2016) - Palmlöf, L.; Holm, L. W.; Alfredsson, L.; Skillgate, E.
Abstract: Background: Expectations have been investigated in populations seeking care for neck pain, however not considering potential confounding factors. The aim of this study was to investigate if pretreatment expectations of recovery is a prognostic factor for recovery from neck pain at 7 weeks follow‐up in patients seeking manual therapy treatment. Method: The study was based on the Stockholm Manual Intervention Trial, a randomized controlled trial investigating efficiency of three combinations of manual therapy. The patients with neck pain were included in this study ( n = 716). Expectations of recovery was measured at baseline; 'How likely is it, according to your judgment, that you are completely recovered from your neck/back problems in 7 weeks'. Patients answered on a 11‐point scale, further categorized into low, moderate and high expectations. The outcome was measured at 7 weeks follow‐up by a modified version of the Global Perceived Recovery Question. Potential effect measure modifiers and confounders were measured at baseline. Multivariable log binomial regression models were used to analyse the association between expectations and recovery, presented as relative risks and 95% confidence intervals (CI). Results: High expectations of recovery yielded a 47% increased probability of being recovered at 7 weeks follow‐up. High expectations of recovery yielded improved recovery in both men and women separately, but moderate expectations yielded improved recovery only among men. Conclusion: Our results suggest that expectations of recovery is a prognostic factor for recovery in patients with neck pain seeking manual therapy treatment. What does this study add?: We found that high expectations of recovery yielded a higher probability of recovery compared to having low expectations, also when considering potential confounding factors. Expectations seemed to have a more distinct influence on recovery among men.